Multi-decadal geodetic mass balance, climate sensitivity, and projected glacier response in the Chandra–Bhaga Basin, Western Indian Himalaya (1971–2100) - Bhattacharya, Atanu; Paul, Ankita; Mukherjee, Kriti; Khatun, Julekha; Ghuffar, Sajid; Bolch, Tobias (Elsevier, 2026)
Glaciers in the Chandra–Bhaga basin, western Indian Himalaya, are critical to the cryosphere–hydrosphere system, yet their long-term climate responses remain poorly understood due to sparse in-situ data. Our geodetic mass balance assessment reveal substantial ice loss from 1971 to 2022, with glaciers shrinking by 0.72 ± 0.08 km2 a−1 and losing mass at 0.26 ± 0.10 m w.e. a−1. Debris-covered glaciers experienced greater ice loss (0.28 ± 0.10 m w.e. a−1) than clean-ice glaciers (0.20 ± 0.12 m w.e. a−1). CMIP6-based regression indicates modest pre-2000 loss, then average loss rates of −0.5 m w.e. a−1 until ∼2035, after which trajectories diverge depending on SSP scenarios. Temperature sensitivity is strongest in summer (−0.49 m w.e. a−1 °C−1) and weakest in winter (−0.38 m w.e. a−1 °C−1). Precipitation sensitivity is highest for winter and lowest for summer. ERA5 Land reanalysis-based sensitivities show annual temperature has stronger influence than seasonal, with lower magnitudes than CMIP6. Winter precipitation from ERA5 Land reanalysis data show stronger correlation to glacier mass gain compared to CMIP6. These differences emphasize uncertainty over which dataset better represents regional climate, particularly for temperature–mass balance relationships and winter precipitation that largely governs glacier accumulation. Despite this, sensitivities align with broader Himalayan trends. Projections suggest stable winter precipitation, combined with increased summer and annual warming, will accelerate mass loss through the 21st century. This study proves that long-term geodetic data can provide an alternative solution to understand glacier–climate interactions in data-scarce regions such as the Himalaya, enabling reconstructions, forecasts, and targeted adaptation for glacier-dependent communities.
Keywords: 37 Earth Sciences; 3709 Physical Geography and Environmental Geoscience; 3702 Climate Change Science; 13 Climate Action; Environmental Sciences; Glacier mass balance; Climate sensitivity; High Mountain Asia (HMA); Remote sensing; Future projections (SSP scenarios)